ANALISIS PENANGANAN HASIL TANGKAPAN KAPAL PURSE SEINE DI KABUPATEN BANTAENG - Herawanty Herawanty; Andi Asni; Ernaningsih Ernaningsih (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
The purse seine is the dominant fishing tool at the Birea Fish Landing Base (FLB) which generally catches small pelagic fish. Handling fresh fish is an important part of the chain of the fishing industry. The problem that dominates fishermen and owners is the decline in the quality of fish caught due to fishing time at sea, so that preservation technology is needed that is able to maintain the quality of the fish longer from being caught until landed in the fishing port.The purpose of this study was to analyze the handling and quality of the purse seine fish catch and to analyze the handling and quality of the fish catch after landing from the purse seine ship. This research was conducted on a purse seine vessel in Bantaeng Regency from February to March 2020. Of the five vessels that were the object of research, vessels with better fish quality were vessels that used management with a ratio of 1: 1 meaning 1 kg for 1 kg of fish. The behavior management of fish traders in the market and the travel time from the fish caught to the market are factors that influence the effect of the decline in fish quality.